2007
DOI: 10.1093/ndt/gfl748
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of central and obstructive sleep apnoea in haemodialysis patients

Abstract: There is a high prevalence of SA in haemodialysis patients. The dominant type of SA in haemodialysis patients is obstructive sleep apnoea (OSA). Uraemia (BUN, Cr), metabolic acidosis (serum bicarbonate) and BMI are good predictors of OSA. PaO2, PaCO2 and CTR are good predictors of central sleep apnoea (CSA). Good management of these factors might improve SA in haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 20 publications
3
50
0
6
Order By: Relevance
“…Our findings support that the prevalence and severity of OSA among nondialysis CKD patients is considerably higher than those in the general population, in which 1 of 5 adults suffers mild OSA and 1 of 15 has moderate OSA (1). The number of central sleep apnea events in our population was modest and comparable to or slightly less than that previously observed among hemodialysis patients (20,21). It is notable that in this study subjects were enrolled irrespective of sleep complaints and showed a high prevalence of OSA.…”
Section: Discussionsupporting
confidence: 66%
“…Our findings support that the prevalence and severity of OSA among nondialysis CKD patients is considerably higher than those in the general population, in which 1 of 5 adults suffers mild OSA and 1 of 15 has moderate OSA (1). The number of central sleep apnea events in our population was modest and comparable to or slightly less than that previously observed among hemodialysis patients (20,21). It is notable that in this study subjects were enrolled irrespective of sleep complaints and showed a high prevalence of OSA.…”
Section: Discussionsupporting
confidence: 66%
“…They found a meaningful relation between the neck base circumference and the incidence of sleep apnea syndrome (25). The prevalence of the sleep apnea syndrome reported in previous studies ranges between 11.8% and 73.5% (2,4,10,20,26). In our study, 23.19% of the patients had experienced sleep apnea syndrome.…”
mentioning
confidence: 47%
“…156 Volume overload and the specific redistribution described in patients with ESRD may be not only a consequence but also an important cause of obstructive sleep apnea. 157 …”
Section: Nonvolume-dependent Causes Of Hypertension In Dialysis Patientsmentioning
confidence: 99%